The population structure of Staphylococcus aureus in China and Europe assessed by multiple-locus variable number tandem repeat analysis; clues to geographical origins of emergence and dissemination. (January 2016) - Yan, X.; Schouls, L.M.; Pluister, G.N.; Tao, X.; Yu, X.; Yin, J.; Song, Y.; Hu, S.; Luo, F.; Hu, W.; He, L.; Meng, F.; et al.
Abstract: To compare the genetic population structure of Staphylococcus aureus from China and Europe, 1294 human isolates were characterized by multiple-locus variable number tandem repeat analysis (MLVA). In total, MLVA identified 17 MLVA complexes (MCs), comprising 260 MLVA types (MTs) among the Chinese isolates and 372 MTs among the European isolates. The five most frequent MCs among the Chinese isolates belonged to MC398, MC5 subclade a, MC8, MC437 and MC7 and made up 55% of the sample. For the European isolates, the five most frequent MCs consisted of MC5 subclade a, MC45, MC8, MC30 and MC22, which accounted for 64% of the sample. Phylogeographic analysis of the major MCs shared between China and Europe points to a European origin of MC8 but cannot provide a consistent signal for MC5 subclade a, probably indicating a different origin. Diversity and frequency distributions of other lineages were also compared. Altogether, this study provides the first snapshot of two extant populations of S. aureus from Europe and China, and important clues on the emergence and dissemination of different lineages of S. aureus.